Profile required in public notices and public tenders for the position of Technician in Cytopathology (Research, Society and Development, 2023)
The cytopathology technician has an important role in supporting the diagnosis of microscopic examinations working in pathological anatomy and cytopathology laboratories. The lack of standardization of courses and in-service training marked the health training process of these professionals. Only in 2010 was the first Ministry of Health guideline launched for the training of these professionals, contemplating the merger of the technical area of cytopathology with histotechnology. The objective of the study was to identify curricular contents addressed in public exams for technicians in cytopathology. Analysis of tests and public notices between 2012 and 2022 was carried out. The cytopathology thematic category had the highest number of questions (38.5%), followed by histotechnology (24.7%). Among the cytopathology contents, the gynecological cytology category (50.5%) had the highest number of questions. In histotechnology content, the histological techniques category (62.9%) stood out. The increase in histotechnology content in tests reflects changes in guidelines and guidelines for training these professionals, requiring adjustments in technical courses.